Optimal configuration method based on optimal expected power characteristics for micro power supply and energy storage device. Issue 16 (28th September 2018) - Xiao, Huagen; Yi, Xiaoyu; Ding, Shiqi; Su, Shi
Abstract : In this study, an optimal configuration method based on optimal expected power characteristics for micro power supply and energy storage device is proposed, which takes the minimum average fluctuation rate of the total output power characteristics of renewable micro power supply and microgrid as the optimisation objective, respectively. The proposed method can improve the smoothness of the total output power characteristics of the renewable micro power supplies, and effectively reduce the maximum adjustable power and available capacity of the energy storage devices. At last, the feasibility and effectiveness of the proposed method are verified by the case study results.